Information technology governance in University of Muhammadiyah Palembang using framework COBIT 5 domain; Evaluate, Direct and Monitor (EDM) - Elsi, Zulhipni Reno Saputra; Karnadi, Karnadi; Jimmie, Jimmie; Putra, Fajrie Agus Dwino; Hartini, Hartini; Agustanti, Sri Primaini (ILKOM Jurnal Ilmiah, 2022)
This study aims to find out about Information Technology management at Muhammadiyah University of Palembang and to get right advice in managing Information Technology from the University level to the Study Program. Regarding benchmarks in Information Technology Governance use the Cobit 5 framework with the Evaluate, Direct and Monitor domains. Monitoring and evaluation was carried out using a questionnaire distributed to lecturers and employees at the Muhammadiyah University of Palembang and the researchers did observations on the management of higher education information technology governance. Based on the questionnaire result, the highest gap occurs in sub domain 4, which is 3.65 while the observation result towards the capability level is at level 3 with a value of 56.67%, the sub domain ensuring resource optimization has the highest capability value of 66.67%. Based on the data obtained using the EDM domain, the University of Muhamadiyah Palembang has to set Standard Operating Procedures (SOP) and Work Instructions (IK) so every five processes can run well to create good IT governance.